(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Today is a digital world where information in available digitally in no time. Libraries are not exception of it. Traditional libraries have turned into digital libraries. The major role behind this revolution is the Information and communication technology. ICT have impact in almost every field. In libraries all the library working whether it is acquisition, circulation, cataloguing, dissemination and retrieval of information everything has totally changed from manually to digitally. Information can be access from anywhere and anytime. As ICT brings opportunities it brings challenges also. It also impact on the level of job satisfaction. This paper studies the variables that affect the job satisfaction in this ICT environment in the public libraries of Chandigarh.